Youth Employment in Rural Albania: A Theoretical Approach - Manuela Mece (European Scientific Journal, ESJ, 2016)
Employment plays a central role in the social integration of young people. Young people in rural areas are the future of agriculture and other rural industries, but often lack the guidance and support necessary to fully contribute to the development of their communities, thereby fuelling the vicious cycle of rural underdevelopment and poverty. This study aims to gain a better understanding of the youth employment challenges faced in rural areas by bringing together in group discussions with stakeholders (farmers, entrepreneurs in rural areas, associations, etc.). The conclusions from this assignment will feed to a baseline analysis of youth involvement in rural labour market and skills development required and will identify areas where rural development programs can be targeted to increase their contribution to employment creation. This will also suggest formulation of policy recommendations on stimulating new sources of employment, and the conditions for success in stimulating employment in rural areas. The proposed methodology was developed through Desktop Research and direct interviews with focus groups.